Authentication Security of Combinatorial Watermarking for GNSS Signal Authentication - Jason Anderson; Sherman Lo; Todd Walter (Navigation)
Watermarking signal authentication is a technique in which a global navigation satellite system (GNSS) provider cryptographically perturbs the spreading code to allow for limited cryptographic authentication of a signal. Several proposals and studies have been presented or are underway to augment GNSS signals with this capability. This work reintroduces a generalized combinatorial watermarking function that affords a flexible pathway to cryptographically prove the authentication security of a signal with receiver observables under certain assumptions. The security levels are comparable to those of standard cryptographic security (e.g., 128-bit security) and require little or no additional use of the navigation data bandwidth. We show how our methods can be applied to signals of different designs and signal-to-noise ratios. With our receiver processing strategy, one can design a watermarking signal authentication scheme and the accompanying receiver to have high confidence in a signal’s authenticity.